2021
DOI: 10.3390/app112211063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Collagen-I Coatings of 3D Printed PCL Scaffolds for Bone Replacement on Three Different Cell Types

Abstract: Introduction The use of scaffolds in tissue engineering is becoming increasingly important as solutions need to be found to preserve human tissues such as bone or cartilage. Various factors, including cells, biomaterials, cell and tissue culture conditions, play a crucial role in tissue engineering. The in vivo environment of the cells exerts complex stimuli on the cells, thereby directly influencing cell behavior, including proliferation and differentiation. Therefore, to create suitable replacement or regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…This captures both images of the surface and laser scans. Surface-specific values such as surface roughness (center roughness Sa) can then be measured, analogous to our previous work [ 11 , 14 ]. To investigate the surface roughness before and after plasma treatment of the scaffolds, images were acquired using the 3D laser microscope and the surface roughness was measured at four random locations.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…This captures both images of the surface and laser scans. Surface-specific values such as surface roughness (center roughness Sa) can then be measured, analogous to our previous work [ 11 , 14 ]. To investigate the surface roughness before and after plasma treatment of the scaffolds, images were acquired using the 3D laser microscope and the surface roughness was measured at four random locations.…”
Section: Methodsmentioning
confidence: 95%
“…The PCL scaffolds were manufactured by using a 3D-BioPlotter (EnvisionTEC, Gladbeck, Germany) according to our previous work [ 11 , 14 ]. For this purpose, a 3D model of the scaffold was created in Autodesk Inventor (Autodesk Inventor 2019; Autodesk, San Raphael, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Kim [ 41 ] achieved similar surface roughness values of 2.4 ± 0.2 µm with their self-healing collagen coatings, after treatment with water. In our previous work, we showed that the uncoated scaffolds had a surface roughness of 4.11 ± 0.27 µm and the collagen-coated samples had a roughness of 3.35 ± 0.3 µm [ 34 ]. The scaffolds were square, with a line infill.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate serum esterase activity, all samples at a specific time point had the medium removed and the cells washed. Staining was then performed according to a previously published protocol [ 34 ]. The evaluation was performed using an Olympus fluorescence microscope (BX51, Olympus, Osaka, Japan) at 5 different positions on the samples, at 5× and 10× magnification.…”
Section: Methodsmentioning
confidence: 99%